2020
DOI: 10.3389/fphys.2019.01577
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepcidin Levels During a Period of High Training Load Do Not Alter Iron Status in Male Elite Junior Rowers

Abstract: The liver-derived hormone hepcidin plays a key role in iron metabolism by mediating the degradation of the iron export protein ferroportin 1 (FPN1). Circulating levels of hepcidin and the iron storage protein ferritin are elevated during the recovery period after acute endurance exercise, which can be interpreted as an acute phase reaction to intense exercise with far-reaching consequences for iron metabolism and homeostasis. Since absolute and functional iron deficiency (ID) potentially lead to a loss of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
3
11
0
Order By: Relevance
“…Also in rowers, acute inflammatory responses to training are associated with decreased aerobic performance (VO 2 max and maximal aerobic power; Jürimäe et al, 2016). In line with that we previously showed that hepcidin and ferritin, both representing acute-phase proteins, are sensitive to initial increases in training load after seven days during a training camp (Zügel et al, 2019). Also, in the present study, we found slightly increased ferritin levels during COMP, which were not associated with significantly increased IL-6 levels.…”
Section: Discussionsupporting
confidence: 80%
“…Also in rowers, acute inflammatory responses to training are associated with decreased aerobic performance (VO 2 max and maximal aerobic power; Jürimäe et al, 2016). In line with that we previously showed that hepcidin and ferritin, both representing acute-phase proteins, are sensitive to initial increases in training load after seven days during a training camp (Zügel et al, 2019). Also, in the present study, we found slightly increased ferritin levels during COMP, which were not associated with significantly increased IL-6 levels.…”
Section: Discussionsupporting
confidence: 80%
“…This may reflect the players’ adaptation to the applied exercise load. Zügel et al [ 49 ] analysed the cumulative effect of training stress in highly qualified athletes practising rowing, focusing on hepcidin and parameters related to iron management. The authors showed that the levels of hepcidin and ferritin, acute-phase proteins, were a sensitive indicator of changes in the training load (exercise volume and intensity).…”
Section: Discussionmentioning
confidence: 99%
“…Zügel et al analysed the cumulative effect of training stress in highly quali ed athletes practising rowing on the level of hepcidin and its impact on parameters related to iron management. They showed that the levels of hepcidin and ferritin as acute-phase proteins were a sensitive indicator of changes in training loads (increase in volume and intensity of exercise) [44]. In the above study, football players were subjected to the same training loads throughout the entire study period, which probably explains the lack of statistically signi cant differences in the levels of hepcidin and ferritin .…”
Section: Discussionmentioning
confidence: 83%